Palliative care and quality of life - Lavado-Salinas, Martha Enriqueta R. (2022)
Palliative care represents an approach that improves the quality of life and well-being of patients and families who go through an illness, alleviating physical, psychosocial and spiritual suffering; with adequate information on their state of health, reinforcing human dignity through the principles of bioethics; it should be included in the entire care process starting from primary care. Health professionals have the commitment and ethical responsibility to mitigate pain and suffering regardless of the prognosis, evaluating the quality of life of the chronic patient, the impact of the disease, their adaptation to it, knowing how the treatment and the possible effects adverse events affect the evolution process, developing patient communication strategies to help decision-making.